Feasibility and techno-economic analysis of stand-alone and grid-connected PV/Wind/Diesel/Batt hybrid energy system: A case study. (September 2021) - Das, Barun K.; Alotaibi, Majed A.; Das, Pronob; Islam, M.S.; Das, Sajal K.; Hossain, Md Alamgir
Abstract: In this study, the economic and environmental benefits of stand-alone and grid integration are thoroughly analyzed with different system configurations of a PV/Wind/Diesel/Battery based hybrid energy system (HES) for five different climatic regions using hybrid optimization model for electric renewables (HOMER). A detailed techno-economic study of optimized hybrid systems is further examined by integrating the grid-connected option. The environmental benefits of HESs are discussed. The sensitivity of various sell-back price to the national grid is also investigated. Additionally, the barriers and opportunities of installing such projects in the off-grid regions are discussed. Results indicate that the cost of energy (COE, $/kWh) and the net present cost (NPC, $) of the stand-alone hybrid PV/Diesel/Battery for the Rajshahi region are slightly lower compared to other areas, considering the cost and environmental emissions. The same system in Chattogram shows great potential both financially and environmentally, over the other climatic zones. The grid-connected HES with the sell-back option offers significant cost-benefits (0.07$/kWh), even over the grid tariff (0.10$/kWh). Similar revenues can be attained with the grid-connected PV/Battery-based system as substantial amount of excess energy could be supplied to the grid facilities. In the grid integrated HES, around 45, 582 kg-CO2 /yr could be saved compared to grid only system, whereas this amount is 32, 905 kg-CO2 /yr over the stand-alone hybrid PV/Diesel/Battery one. Highlights: The study investigates stand-alone hybrid PV/Diesel/Batt and grid-connected options. Rajshahi region has the lower COE (0.28$/kWh) than the other region studied. Grid-connected hybrid PV/Diesel/Batt option provides significant cost benefits. Grid sell-back tariff higher than the grid purchase identifies a profitable venture. Grid-connected hybrid system significantly reduces CO2 over grid-connected one.